Thomas Dodd interview with Captain William R. Anderson, National Service Corps (Domestic Peace Corps) - Dodd, Thomas J. (Thomas Joseph), 1907-1971 (Creator); Anderson, William R., 1921-2007 (Creator) (1963)
Thomas Dodd asks Captain Anderson about the purpose and programs of the National Service Corp--a domestic program modeled on the Peace Corps. Anderson describes the program as a group of dedicated and trained individuals working with a "people to people program" to address the urgent problems of the people in need in this country. Dodd asks if it is necessary that this be addressed at the federal level and the response is that even the professionals working at the local level admit that they cannot handle the issues within their own communities and a national program is necessary. Planned programs include working on mental health, those with developmental challenges, the Native American communities, as well as migrant workers and those in the inner cities. Archives & Special Collections, University of Connecticut Library William R. Anderson; b. William Robert Anderson, June 17, 1921, Bakerville, Tenn.; d. Feb. 25, near his home in Leesburg, Va., aged 85; commanded the nuclear-powered submarine Nautilus on its historic cruise beneath the North Pole in August 1958 and later served three terms in Congress. (LOC NAF, https://lccn.loc.gov/n82059182; accessed 2022-06-07) Thomas J. Dodd Papers MSS 1994.0065